Nick Levett on talent development - Levett, N. (Supporting champions, 2020)
Have you ever found yourself stood along side parents or coaches shouting and barking instructions to their child? Or have you ever found yourself bursting out with commands or subtly taking your child aside to say, "Just do this". If we have done this or seen this or felt the urge to help but done so in a clumsy way - then we`ve been an influence (perhaps not positive) on a child`s interest in not only sport but on their willingness to try.